Addressing the educational crisis in Cameroon: Policy syndromes, arguments, views, theory and agenda - Elvis D. Achuo; Simplice Asongu; Gildas D. Dinga (African Governance and Development Institute (AGDI), 2022)
This study pursues two main objectives. Firstly, we sought to unravel the key factors at the origin of the educational crisis in Cameroon. Second, we sought to identify the major causes of the mismatch between educational attainment and the job market. The study reveals the educational sector and educational management constitute the major causes of the educational crisis in Cameroon. Moreover, in order to address the crisis, we propose a novel theoretical model 'The Education and Job Mismatch Crisis Hypothesis', wherein educational crisis is a function of employment, ability to grow and remuneration. Contingent on the findings of this study, we recommend that the Cameroon government should aggregate various existing educational ministries into a single ministry of education. Besides, the unique ministerial department should envisage the creation of separate directorates in charge of the English and French sub-systems of education that coexist in Cameroon.
Keywords: 330; Educational crisis; Educational system; Educational management; Job-mismatch; EJMC hypothesis; Process tracing